Cloning And Characterization Of An Unusual Polyhydroxyalkanoate Acid Synthase (phaC) Gene From A Chromobacterium Sp. Isolated Locally - Kam, Yew Chee (2009)
Chromobacterium sp. is a bacterium capable of producing polyhydroxyalkanoates (PHA). The Chromobacterium sp. PHA synthase (PhaC) is able to polymerize shortchain- length PHA monomers, such as 3-hydroxybutyrate and 3-hydroxyvalerate. Chromobacterium sp. ialah bakteria yang berupaya mensintesis polihidroksialkanoat (PHA). PHA sintase (PhaC) Chromobacterium sp. berupaya mempolimerisasikan monomer PHA berantaian pendek seperti 3-hidroksibutirat dan 3-hidroksivalerat.